Structural studies on a family of cAMP-binding proteins in the nervous system of Aplysia (The Rockefeller University Press, 1986)
Five major cAMP-binding proteins that differ in size and charge have been identified in neurons of Aplysia californica by photoaffinity labeling with [32P]8-N3cAMP. These proteins, which we believe are regulatory subunits of cAMP-dependent protein kinase, all differ from the major cAMP-binding protein of buccal muscle. We have compared the structures of these proteins by peptide mapping after chemical and proteolytic cleavage. These analyses indicate that the five binding proteins from nervous tissue and the major muscle protein are closely related to each other. For example, the three neuronal proteins that are most alike and the cAMP-binding protein from muscle have a similar, if not identical, Mr 20,000 domain that contains the 8-N3cAMP-binding site; beyond this domain they diverge. All six proteins appear to belong to a family in which homologous regions have been conserved to maintain common functions. We suggest that the regions of the molecules that differ mediate special functions such as ticketing to particular compartments of the cell. Evidence for regional assortment of the cAMP- dependent protein kinases according to structural type was afforded by subcellular fractionation of Aplysia nervous tissue; photoaffinity labeling of cytoplasm, cytoskeleton, and membrane fractions demonstrated a differential distribution of the five neuronal cAMP- binding proteins. Selective phosphorylation of specific substrates could be a consequence of the compartmentation of diverse cAMP- dependent kinases.